Communication skills in clinical practice a video guide - Buckman, Robert; University of Calgary (Toronto, Canada : Distributed by Medical Audio Visual Communications, 1999)
Includes scenarios with simulated patients illustrating various clinical situations, communication problems and approaches to dealing with them.
Tape #2. Dealing with feelings (55 min., 30 sec.) -- tape #4. How to break bad news (79 min.)
Written by Robert Buckman, Walter Baile, Barbara Korsch
Keywords: Physician-Patient Relations; Communication